HUBUNGAN KEBIASAAN MEROKOK DENGAN KETAHANAN KARDIORESPIRASI PADA DOSEN PRIA FAKULTAS ILMU SOSIAL DAN ILMU POLITIK UNIVERSITAS RIAU - ELI ERAWATI; MIFTAH AZRIN; INDRA YOVI (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2014)
Cardiorespiratory endurance is ability of heart system, lungs and blood vesselsto optimal function when do daily activity in long time without serious tired.Cardiorespiratory endurance influenced some factors such as: age, sex, nutritionalstatus, sport and smoke habits. Harvard step test is one of cardiorespiratory enduranceinspection that can do in the field with use simple tools, cheap, and easy to do by allpeople. This research is the analytical research with cross sectional approach thatpurpose to know the relation of smoke habits with cardiorespiratory endurance of manlecturer in social and politicies faculty in riau university by taking over sample technicsis total sampling. There are 40 man lecturers in 45-65 years old, but 31 of them fillinclude criteria. The result of research show there are relation that meaning betweensmoke habits and cardiorespiratory endurance with medium correlation strong anddirection negative correlation (r=-0,497 ; p=0,001). Conclusion in this research is mostof man lecturer have smoke habits in medium smoker category with enoughcardiorespiratory endurance.Keywords : smoke habits, cardiorespiratory endurance